Study the role of the religious beliefs on general health status of the members of pensioners association of Guilan University of Medical Sciences - Rasht - Shadman Reza Masouleh; Farzaneh Sheikhol Eslami; Naema Khodadadi; Mohammad Ali Yazdani (Guilan University of Medical Sciences, 2010)
Introduction: World population is getting old. Regarding the increasing number of elderly individuals and prevalent mental disorders, seeking other sources in order to prevent the difficulties of geriatric conditions is necessary. It seems that religion can play an important role in supporting the elderly in reducing the mental disorders and making meaningful life. Objective: The aim of this study was to determine the role of internal and external religious beliefs in general health of the elderly members of pensioners association of Guilan University of Medical Sciences – Rasht. Methods: This study was a descriptive – correlational research. Sampling performed, through easy sampling method. 100 members of pensioner association from both gender (female and male) took part in the study. Data collection instrument was a questionnaire consisted of three parts. Part one was about demographic Data, Part two about internal and external religious beliefs of Aloport and part three was about general health status with 28 questions. Data were analyzed by descriptive-analytical methods, using SPSS. Results: The research findings indicated that external religious beliefs, has strong correlation with visiting relatives and social activities. Internal religious beliefs correlates with emotional supports received from family members and others (P < 0.05). Non- parametric statistical test revealed a significant correlation between internal religious belief and general health (P < 0.05). Conclusion: It was demonstrated that religious beliefs as an important source of support can help elderly people to achieve better physical and mental health. These findings should be considered in mental health education programs.